Radical Scavenging Capacity of hop-derived Products - Van Hoyweghen, Laura; Biendl, Martin; Heyerick, Arne (BrewingScience, 2010)
Dietary antioxidants are believed to be effective in the prevention of oxidative stress related diseases (eg. cancer and cardiovascular diseases). Polyphenols are widely recognized as potent antioxidants as they can scavenge reactive oxygen species (ROS). The hop plant (Humulus lupulus L.), used in a variety of health applications and indispensible as a beer ingredient, is an interesting source of polyphenolic antioxidants including tannins, flavonol glycosides and prenylated fl avonoids. In addition, also hop oil and hop acids (including downstream products) have been reported as potent antioxidants. In this investigation, the radical scavenging activity of hop products (including different extracts and downstream products) was investigated using two different antioxidant assays: the ORAC to study the peroxyl radical scavenging capacity and HORAC to investigate the hydroxyl radical scavenging capacity. Quercetin and a grape extract containing oligomeric proanthocyanidins (OPC) were used for comparison. The peroxyl radical scavenging capacities of prenylated fl avonoids were highly analogous to quercetin and OPC equaling 5–10 Trolox equivalents. The hydroxyl radical scavenging capacities of Xantho-FlavTM products correlated with the concentration of xanthohumol and pure xanthohumol (> 95 %) corresponded to about 60 Trolox equivalents, which is 10–20 times higher than that of quercetin and OPC. Consistently, ethanol extracts showed a higher radical scavenging activity than CO2-extracts. Furthermore, tannin extract proved an efficient peroxyl radical scavenger. Thus it can be concluded that xanthohumol-containing products show high radical scavenging capacities, which partly may be mediated by its metal ion chelating properties. Apart from their possible health benefits, these products might also contribute antioxidant power during the brewing process and during storage.